-7d-1-5=-1-2d

Simple and best practice solution for -7d-1-5=-1-2d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7d-1-5=-1-2d equation:


Simplifying
-7d + -1 + -5 = -1 + -2d

Reorder the terms:
-1 + -5 + -7d = -1 + -2d

Combine like terms: -1 + -5 = -6
-6 + -7d = -1 + -2d

Solving
-6 + -7d = -1 + -2d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '2d' to each side of the equation.
-6 + -7d + 2d = -1 + -2d + 2d

Combine like terms: -7d + 2d = -5d
-6 + -5d = -1 + -2d + 2d

Combine like terms: -2d + 2d = 0
-6 + -5d = -1 + 0
-6 + -5d = -1

Add '6' to each side of the equation.
-6 + 6 + -5d = -1 + 6

Combine like terms: -6 + 6 = 0
0 + -5d = -1 + 6
-5d = -1 + 6

Combine like terms: -1 + 6 = 5
-5d = 5

Divide each side by '-5'.
d = -1

Simplifying
d = -1

See similar equations:

| 3x=19-(8x-14) | | 24-9(2)= | | 25+7p=12p | | COT(O)=-0.085 | | 8m+33=7+5(4m-2) | | -2v-8=-3v | | 18x=84-(7x+9) | | cot=-0.085 | | -19q+8(-4-7q)= | | x^2+kx+x+2k=0 | | x^3-9x=-6 | | 7-9j=4j-6 | | 7x=21-(49x-63) | | x^2-4x+y^2+z^2-6z-3=0 | | T^2+16t-36=0 | | 5-8u=-7u | | 8t-9=10t+9 | | 5x=31+2x+11 | | 6x+10-3x=8+2x-5 | | -r^2+8r=0 | | 2cosx-5=0 | | 3y+9=2y-4 | | 6+10-3x=8+2x-5 | | Y=5z-8 | | 15x+3(4x-6)=3x+9-9x | | (2x-4)+X=28 | | 7x=5+3x+19 | | 8h=10h+6 | | x^2-2x=19 | | 20+7n-6=7(2n+4) | | (x+14)(2x-7)=0 | | -5g=-10-3g |

Equations solver categories